2013
DOI: 10.1177/0272431613507498
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Change and Time-Specific Variation in Global and Specific Aspects of Self-Concept in Adolescence and Association With Depressive Symptoms

Abstract: Previous research has demonstrated that adolescents make differential self-evaluations in multiple domains that include physical appearance, academic competence, and peer acceptance. We report growth curve analyses over a seven year period from age 9 to age 16 on the six domains of the Harter Self-Perception Profile for Children. In general, we find little change in self-concept, on average, but do find substantial individual differences in level, rate of change, and time-specific variation in these self- eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 81 publications
8
42
0
Order By: Relevance
“…Finally, statistically significant gender differences were found in some grades, males scoring higher in self‐esteem, math, physical abilities, physical appearance, emotional stability, and parent relationships; and females scoring better in verbal and general school. These results confirm some previous research in self‐esteem (Kling et al., ; Marsh, ; Pastor et al., ; Steiger et al., ; Wilgenbusch & Merrell, ), math (Marsh, ; Marsh et al., ; Nagy et al., ; Wilgenbusch & Merrell, ), physical abilities and physical appearance (Avsec, ; Gentile et al., ; Inglés et al., ; Kling et al., ; Kuzucu et al., ; Marsh, ; Marsh et al., ; Pastor et al., ; Wilgenbusch & Merrell, ; Young & Mroczek, ), emotional stability (Avsec, ; Inglés et al., ; Marsh, ; Marsh et al., ; Wilgenbusch & Merrell, ), parent relationships (Marsh et al., ), verbal (Marsh, ; Marsh et al., ; Nagy et al., ; Wilgenbusch & Merrell, ), and general school (Coelho et al., ; Young & Mroczek, ), and are consistent with sex stereotypes which impact individuals’ self‐concept formation—that is, both genders score higher on self‐concept dimensions that are stereotypically associated with their gender.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Finally, statistically significant gender differences were found in some grades, males scoring higher in self‐esteem, math, physical abilities, physical appearance, emotional stability, and parent relationships; and females scoring better in verbal and general school. These results confirm some previous research in self‐esteem (Kling et al., ; Marsh, ; Pastor et al., ; Steiger et al., ; Wilgenbusch & Merrell, ), math (Marsh, ; Marsh et al., ; Nagy et al., ; Wilgenbusch & Merrell, ), physical abilities and physical appearance (Avsec, ; Gentile et al., ; Inglés et al., ; Kling et al., ; Kuzucu et al., ; Marsh, ; Marsh et al., ; Pastor et al., ; Wilgenbusch & Merrell, ; Young & Mroczek, ), emotional stability (Avsec, ; Inglés et al., ; Marsh, ; Marsh et al., ; Wilgenbusch & Merrell, ), parent relationships (Marsh et al., ), verbal (Marsh, ; Marsh et al., ; Nagy et al., ; Wilgenbusch & Merrell, ), and general school (Coelho et al., ; Young & Mroczek, ), and are consistent with sex stereotypes which impact individuals’ self‐concept formation—that is, both genders score higher on self‐concept dimensions that are stereotypically associated with their gender.…”
Section: Discussionsupporting
confidence: 89%
“…However, there are some inconsistencies in the literature and other studies have found that scores in self‐esteem increase during adolescence (Steiger, Allemand, Robins, & Fend, ; Vicent et al., ), from middle adolescence to young adulthood (Birkeland, Melkevik, Holsen, & Wold, ; Bleidorn et al., ; Erol & Orth, ; Kiviruusu et al., ; von Soest, Wichstrøm, & Lundin Kvalem, ) and from middle adolescence to old age (Meier, Orth, Denissen, & Kühnel, ). Other studies have not found differences in adolescents (Kuzucu, Bontempo, Hofer, Stallings, & Piccinin, ; Pastor, Balaguer, & García‐Merita, ; Young & Mroczek, ), claiming that for the majority of students (69.7%) global self‐esteem remains stable across Grades 7–10 (Morin, Maiano, Marsh, Nagengast, & Janosz, ) and concluding that the mean self‐esteem level depends more on the type of the measure used (single vs. 10‐item), sampling method, and measurement error than age (Pullmann, Allik, & Realo, ).…”
Section: The Development Of Self‐concept/self‐esteemmentioning
confidence: 96%
See 1 more Smart Citation
“…Studies have shown that self‐concept is significantly associated with many variables. For example, decreases in all domains of self‐concept over a 7‐year period, from childhood to adolescence, could be predicted from respondents' level of depression (Kuzucu, Bontempo, Hofer, Stallings, & Piccinin, ). Low scholastic, social, and behavioural self‐concepts were linked with high self‐reported bullying behaviour and victimization by peers (Andreou, ).…”
Section: Self‐concept In Adolescencementioning
confidence: 99%
“…In their studies, this decline was found to continue into the seventh grade and to only recover in late adolescence (Eccles et al, ; Wigfield & Eccles, ; Wigfield et al, ). In contrast to this empirical evidence, independent longitudinal studies in early to middle adolescence have demonstrated mean‐level stability (Birkeland et al, ; Bolognini, Plancherel, Bettschart, & Halfon, ; Kuzucu, Bontempo, Hofer, Stallings, & Piccinin, ) or even increases in self‐esteem (Morin, Maïano, Marsh, Nagengast, & Janosz, ; Steiger et al, ). Despite this inconsistency in the developmental direction, all of the cited studies found a substantial amount of interindividual differences in intraindividual change.…”
Section: Introductionmentioning
confidence: 97%